Implementation of the Spiritual Leadership Model in Improving the Quality of Education in Islamic Boarding Schools - Riski, Aulia; Tambunan, Riana; Anggraeni, Novi; Alam, Faisal (JOELS: Journal of Election and Leadership, 2023)
The purpose of this study is to learn more about the use and impact of the school principal's spiritual leadership approach in raising teacher caliber in Islamic boarding schools. This study collected data using descriptive methods and a qualitative approach. Purfocefull technique is used by the sampling technique to obtain data. The Sabiilunnaja Islamic Boarding School in Bandung, West Java, served as the research site for this project. The findings of this study provided information on the spiritual leadership model that the principal of the Sabiilunnaja Islamic Boarding School in Bandung uses in schools to raise teacher quality. The research suggests that if this spiritual leadership model is used in schools, it can enhance leadership, which has implications for enhancing education and reaching predetermined objectives